2022
DOI: 10.1002/pul2.12149
|View full text |Cite
|
Sign up to set email alerts
|

Lack of concordance between the different exercise test measures used in the risk stratification of patients with pulmonary arterial hypertension

Abstract: In pulmonary arterial hypertension (PAH) patients it is essential to perform a prognostic assessment to optimize the treatment. The aim of this study is to evaluate the risk stratification concordance assessed with different exercise test variables in a cohort of PAH patients. A retrospective analysis was performed using patient data registered in the PAH unit. Only those patients in whom the mean time elapsed between the 6‐min walking test (6MWT) and the cardiopulmonary exercise test (CPET) was a maximum of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Young patients with PAH, and even with heart failure, can walk distances greater than 440 m in the 6MWT, and therefore obtain lower scores (distances longer than 440 m score 1 on the 4‐strata scale). In this line, a recent study demonstrated that there is a low level of concordance between the distance walked in the 6MWT and the peak VO 2 in patients with PAH, and a lack of concordance between the different CPET variables used in risk stratification 15 . The younger age of our study population, added to the distance in the 6MWT, reflects the youth and robust status of our population, which clearly depicts a ceiling effect.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Young patients with PAH, and even with heart failure, can walk distances greater than 440 m in the 6MWT, and therefore obtain lower scores (distances longer than 440 m score 1 on the 4‐strata scale). In this line, a recent study demonstrated that there is a low level of concordance between the distance walked in the 6MWT and the peak VO 2 in patients with PAH, and a lack of concordance between the different CPET variables used in risk stratification 15 . The younger age of our study population, added to the distance in the 6MWT, reflects the youth and robust status of our population, which clearly depicts a ceiling effect.…”
Section: Discussionmentioning
confidence: 50%
“…In this line, a recent study demonstrated that there is a low level of concordance between the distance walked in the 6MWT and the peak VO 2 in patients with PAH, and a lack of concordance between the different CPET variables used in risk stratification. 15 The younger age of our study population, added to the distance in the 6MWT, reflects the youth and robust status of our population, which clearly depicts a ceiling effect. Hence, the CPET emerges as a useful tool for these patients.…”
Section: Discussionmentioning
confidence: 77%
“…The absolute values of peak oxygen consumption and peak minute ventilation per unit of carbon dioxide were included in the risk stratification proposed by the ESC/ERS in 2015. However, these parameters have not been widely used due to their low concordance with 6MWT and the interpretation discrepancies between the absolute and predicted values [26]. We observed the comparable absolute values of peak VO 2 , oxygen pulse, and CO 2 ventilatory equivalent in two groups, while the predicted values of peak VO 2 , aerobic threshold, and VO 2 /HR were significantly lower in younger patients in comparison with patients over 60 years.…”
Section: Discussionmentioning
confidence: 52%
“…The absolute values of peak oxygen consumption and peak minute ventilation per unit of carbon dioxide have been included in the risk stratification proposed by the ESC/ERS in 2015. Unless those parameters have not been widely used due to the low concordance with 6MWT and the interpretation discrepancies between the absolute and predicted values [31]. We observed the comparable absolute values of peak VO2, oxygen pulse, and CO2 ventilatory equivalent in two groups, while the predicted values of peak VO2, aerobic threshold, and O2/HR were significantly lower in younger patients in comparison with patients over 60 years.…”
Section: Discussionmentioning
confidence: 52%
“…We have not seen any differences in PVR, cardiac index and PWCP between young and elderly patients, as well as between groups with H2FpEF ≥2 and H2FpEF≤1. PCWP was almost the same for both groups (8.46±4.6 vs 8.9±4.7 mmHg, p=0.6) and was lower compared with PCWP obtained from COMPERA and Swiss registries (10±3 and 12±7 mmHg, respectively) and N. Öcal et al (2022) data [7,31,41]. The majority of patients with H2FPEF score ≥2 are treated with loop diuretics that could reduce PCWP.…”
Section: Discussionmentioning
confidence: 81%